2018
DOI: 10.21608/epsj.2018.17103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Different Guar Meal Levels and Β– Mannanase Supplementation on Productive Performance of Golden Montazah Laying Hens

Abstract: This experiment was carried out to evaluate the effect of dietary guar meal levels with or without β-mannanase on layer performance. One hundred and sixty eight 22-week-old Golden Montazah pullets divided randomly into seven treatment groups each group had 24 pullets divided into three replicates with 8 pullets per each. The 1 st group fed on corn-soybean meal diet and served as control group. The 2 nd , 4 th and 6 th groups fed on diets contain 5%, 10% and 15% guar meal respectively without βmannanase. The 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…In the same manner, guar meal supplementation didn't affect significantly AST and ALT. this result agrees with Youssef and El-Gabry, (2018) who reported that guar meal may not possess an adverse effect on liver function.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the same manner, guar meal supplementation didn't affect significantly AST and ALT. this result agrees with Youssef and El-Gabry, (2018) who reported that guar meal may not possess an adverse effect on liver function.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study supplemented diet with 60 ppm and 120 ppm saponin depressed body fat by 26.9% and 32.6 respectively. The insignificant effects of saponin, salinomycin and guar meal on plasma protein profile were reported by ( Yenge, et al, 2018;Kamashi, et al, 2004;Youssef and El-Gabry, 2018) respectively. Concerning numerical increased in total lipid by salinomycin supplementation, the result is in full agreement with (Angelovičová, et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The effects of guar meal levels on egg yolk index were found to be significant (P < 0.05), while enzyme levels and guar × enzyme interactions did not have any significant effects on yolk index (Table 4). This result is in agreement with the findings of Youssef and Hoda [70].…”
Section: Egg Quality Traitssupporting
confidence: 93%